Compare between Two Methods for Green Synthesis of Silver Nanoparticles - Neeran Obied Jasim (Journal of Global Pharma Technology, 2016)
In this study, compared  between two biological  methods were used for synthesize  Ag nanoparticles , the first used the extract of the conocarpus and the second used Aspergillus niger .Characterized of these nanoparticles was study by UV–vis spectrum(UV), X-Ray diffraction (XRD), scanning electron microscopy (SEM )analysis .Also antimicrobial activity of synthesis nanoparticles were investigation .Results show, used of plant extract  can be considered as the best formulation for the preparation of silver nanoparticles Because of its small particle size, good stability and purity.Keywords: Ag nanoparticles, Green synthesis, Conocarpus extract, A. Niger.